2018
DOI: 10.1002/pmic.201800274
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of LPS‐Induced Macrophage‐Derived Exosomes Indicates Their Involvement in Acute Liver Injury

Abstract: Exosomes are typically involved in cellular communication and signaling. Macrophages play a key role in lipopolysaccharide (LPS)‐induced sepsis. However, the molecular comparison of exosomes derived from LPS‐induced macrophage has not been well analyzed. The macrophage‐exosomes are validated and the protein composition of those exosomes are investigated by isobaric tags for relative and absolute quantification (iTRAQ) mass spectrometry. A total of 5056 proteins are identified in macrophage‐exosomes. We discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 25 publications
0
49
0
Order By: Relevance
“…To examine the effect of LPS treatment on human cardiomyocytes, AC16 cells were treated with increasing concentrations of LPS, which represent varying levels of bacterial infection [18][19][20]. Cell viability was measured after 48 h of LPS treatment.…”
Section: Viability Of Cardiomyocytes After Lps Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the effect of LPS treatment on human cardiomyocytes, AC16 cells were treated with increasing concentrations of LPS, which represent varying levels of bacterial infection [18][19][20]. Cell viability was measured after 48 h of LPS treatment.…”
Section: Viability Of Cardiomyocytes After Lps Treatmentmentioning
confidence: 99%
“…For control cells, exosome-free DMEM/F-12 only was used. The cells Biology 2019, 8, 69 3 of 10 and LPS were incubated for 48 hours (h) without any further manipulation [18][19][20]. The culture media was collected after 48 h.…”
mentioning
confidence: 99%
“…Exosomes are small extracellular vesicles transferring molecular components such as proteins, DNA, and microRNAs (miRNAs) [43]. Exosomes represent an emerging carrier in the delivery of endogenous molecules to regulate gene expression and relevant physiological and pathophysiological processes in recipient cells [26,42,44]. Previous studies demonstrated that suppression of adrenocortical steroid synthesis by a macrophagederived product might be a new regulatory pathway in host response to LPS [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes released from LPS-treated macrophages induced NLRP3 inflammasome and caspase-1 activation of cells in vitro and in vivo, which was associated with the infiltration of macrophages and neutrophils into the tissues (28). The proteomic profiling of the exosomes showed the upregulation of exosomal proteins related with NOD-like receptor signaling pathway (28). A relevant study showed that EVs derived from Staphylococcus aureus activated NLRP3 inflammasome and caspase-1 of human macrophages, which resulted in IL-1β and IL-18 release (29).…”
Section: Nlr/inflammasome Signalingmentioning
confidence: 98%
“…Among the most characterized is NLR family pyrin domain containing 3 (NLRP3) inflammasome, which is a molecular complex known to have potential to activate caspase-1 and induce IL-1β release (27). Exosomes released from LPS-treated macrophages induced NLRP3 inflammasome and caspase-1 activation of cells in vitro and in vivo, which was associated with the infiltration of macrophages and neutrophils into the tissues (28). The proteomic profiling of the exosomes showed the upregulation of exosomal proteins related with NOD-like receptor signaling pathway (28).…”
Section: Nlr/inflammasome Signalingmentioning
confidence: 99%